Formulation peel-off gel mask of Impatiens balsamina l. as an antibactery against Staphylococcus aureus - Fitriani Mahyun; Aris Perdana Kusuma; Hady Anshory (Faculty of Medicine, Universitas Islam Indonesia, 2018)
Background: Acne is a skin disorder characterised by inflammation, accompanied by a blockage of the oil glands in the skin. One of the causes of acne is Staphylococcus aureus bacteria. Many plants have been widely studied as an antibacterial agent, including Garden Balsam Leaf (Impatiens balsamina L.) which could be formulated in a peel-off gel preparation.Objective : The purpose of this research was formulating an antibacterial peel-off gel mask with a variation of viscosity enhancing agent hydroxypropyl methylcellulose (HPMC), as well as testing its antibacterial activity on Staphylococcus aureus.Methods : HPMC 1-2% was formulated in peel-off gel mask of Garden Balsam leaf extract. Physical properties such as viscosity, pH, spreadability, and drying time were tested, while antibacterial activity test was conducted by the agar-diffusion method.Results : The viscosity of the entire formula was > 20,000 cP, pH 6, drying time > 20 minutes, and spreading power > 6 cm. Also, the peel-off gel mask also showed antibacterial activity on Staphylococcus aureus with average inhibition zone were > 10 mm, which indicated strong antibacterial inhibitory power.Conclussion : The concentration variation of HPMC had a significant effect on all physical properties test. HPMC 1.5% in the preparation showed the most optimum results.